Boron-doped graphene-supported manganese oxide nanotubes as an efficient non-metal catalyst for the oxygen reduction reaction - Sookhakian, Mehran; Ullah, Habib; Mat Teridi, Mohd Asri; Goh, Boon Tong; Basirun, Wan Jefrey; Alias, Yatimah (Royal Society of Chemistry, 2020)
An efficient, low cost and non-precious hybrid metal catalyst compound consisting of boron-doped graphene nanosheets (BGNSs) and manganese oxide (MnO2) nanotubes is used as a catalyst for the oxygen reduction reaction (ORR). The morphological and electrochemical properties and chemical composition of the as-synthesized BGNS-MnO2 composite (MnO2@BGNS) were characterized using transmission electron microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, linear sweep voltammetry and a rotating disk electrode (RDE). The as-prepared BGNS-MnO2-modified glassy carbon electrode (GCE) displayed excellent catalytic activity towards the ORR in an alkaline medium compared to pure MnO2 and pure BGNSs. In addition, the hybrid electrode exhibited superior electrocatalytic stability and preferable methanol tolerance compared to commercial platinum electrocatalysts in alkaline media. This is due to the synergistic effect between the excellent catalytic activity of the MnO2 nanotubes and the large surface area and high conductivity of BGNSs. Moreover, density functional theory (DFT) calculations show a strong binding energy between BGNSs and MnO2 in the form of strong electrostatic interaction and inter charge transfer. The enhanced reactivity of MnO2@BGNS is due to the strong bonding between the boron (BGNSs) and oxygen (MnO2). Moreover, the electron density difference and partial density of states (PDOS) analysis suggest that the electron transfer capability of B-O bonding is stronger than that of C-O bonding. Finally, we conclude that boron doping of graphene is an effective strategy for fabricating efficient ORR catalysts. This journal is © The Royal Society of Chemistry.